2021
DOI: 10.1002/adhm.202101557
|View full text |Cite
|
Sign up to set email alerts
|

RNA and Protein Delivery by Cell‐Secreted and Bioengineered Extracellular Vesicles

Abstract: Extracellular vesicles (EVs) are carriers of biological signals through export and delivery of RNAs and proteins. Of increasing interest is the use of EVs as a platform for delivery of biomolecules. Preclinical studies have effectively used EVs to treat a number of diseases. Uniquely, endogenous machinery within cells can be manipulated in order to produce desirable loading of cargo within secreted EVs. In order to inform the development of such approaches, an understanding of the cellular mechanisms by which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 195 publications
0
6
0
Order By: Relevance
“…5,6 EVs are membrane-released vesicles acting as transporters of proteins, lipids, microRNAs (miRNAs or miRs), and long noncoding RNAs (lncRNAs), such as H19. 7,8 H19 is a research focus due to its ectopic expression in various types of human malignant tumors where it exerts oncogenic roles to enhance cell proliferation, invasion, migration, epithelial-mesenchymal transition (EMT), and metastasis as well as impairing chemo and radiotherapy in tumorigenesis, including BC. 9,10 The expression of H19 in paclitaxel (TAX)-resistant TNBC cells is significantly higher than that in TAX-sensitive cells, and H19 knockdown can increase the sensitivity of TNBC cells to TAX by mediating the AKT signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 EVs are membrane-released vesicles acting as transporters of proteins, lipids, microRNAs (miRNAs or miRs), and long noncoding RNAs (lncRNAs), such as H19. 7,8 H19 is a research focus due to its ectopic expression in various types of human malignant tumors where it exerts oncogenic roles to enhance cell proliferation, invasion, migration, epithelial-mesenchymal transition (EMT), and metastasis as well as impairing chemo and radiotherapy in tumorigenesis, including BC. 9,10 The expression of H19 in paclitaxel (TAX)-resistant TNBC cells is significantly higher than that in TAX-sensitive cells, and H19 knockdown can increase the sensitivity of TNBC cells to TAX by mediating the AKT signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has shown that BC exposed to hypoxia (HP) tends to release more extracellular vesicles (EVs) 5,6 . EVs are membrane‐released vesicles acting as transporters of proteins, lipids, microRNAs (miRNAs or miRs), and long noncoding RNAs (lncRNAs), such as H19 7,8 . H19 is a research focus due to its ectopic expression in various types of human malignant tumors where it exerts oncogenic roles to enhance cell proliferation, invasion, migration, epithelial–mesenchymal transition (EMT), and metastasis as well as impairing chemo and radiotherapy in tumorigenesis, including BC 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…[163] Alternatively, the EV surface exhibits diverse options for functionalization with targeting moieties. [64,39,164,165]…”
Section: Pharmacokinetics: Approaches To Control Ev Distribution Afte...mentioning
confidence: 99%
“…Enveloped viruses adopt the reverse process, membrane fusion with the plasma or endosomal membrane, to transfer their proteins and genetic materials into eukaryotic cells ( 163 ). Researchers have also encapsulated protein and nucleic acid cargos into membrane vesicles and delivered them into the cell ( 164 ).…”
Section: Previously Proposed Mechanisms For Translocation Of Folded ...mentioning
confidence: 99%